Change and Continuity in Turkish Foreign Policy: Evaluating Pre-AKP and AKP Periods' National Role Conceptions - Kara, Mehtap; Sozen, Ahmet (Uluslararasi Iliskiler Konseyi Dernegi, 2016)
This article examines Turkish national role conceptions (NRCs) during 1980-2014 based on the policy statements of eighteen Turkish foreign policy-makers. It questions change and continuity in Turkish foreign policy behaviour by evaluating 'pre-AKP' and 'AKP' (Adalet ye Kalkinma Partisi) periods. Role theory is employed as theoretical framework to reveal and assess Turkey's position in global affairs. The NRCs that Turkish foreign policy makers adopted in these periods suggests that there has been both a change and continuity of Turkish foreign policy since 1980.
Keywords: Turkish Foreign Policy; Role Theory; National Role Conceptions